The Conventional Nature of Legal Values - Klimenko, Alexey; Mazurov, Igor (Տիգրան Մեծ)
The article is devoted to the problem of the nature of legal values, the solution of which is of fundamental importance for the construction of legal theories, in one way or another based on the category of “value”. The purpose of this article is to present and substantiate a theoretical model of legal values in the context of a socio-axiological approach to law, involving consideration of the conventional nature of legal values, as well as to characterize the structural and functional relationship of legal values with the legal order and legal culture. When analyzing modern law, the authors use a socio-axiological approach to law, combining sociological and axiological methodology. At the same time, the authors proceed from a materialistic understanding of values. The article also uses general scientific and private scientific research methods. The authors come to the conclusion that law within the framework of modern philosophical and legal analysis from the standpoint of the socio-axiological approach appears as a system of conventional values formed and transformed within the framework of legal discourse. Theoretical understanding of the conventional nature of such values provides an opportunity to consider many aspects of modern legal theory from a new perspective.
Keywords: Socio-axiological approach to law; Philosophy of Law